System of floating solar farm with vertical curtain and different anchoring configuration - Chern, Adam (Nanyang Technological University, 2022)
There has been increasing interest around the world for new and innovative sources of renewable energy. One such source is floating solar farms, or solar farms located in bodies of, usually enclosed, waters. Small countries like Singapore, however, do not have the luxury of large areas of enclosed waters to erect many floating solar farms. Thus, the island nation is starting to explore the coastal waters surrounding her to develop coastal solar farms. Coastal solar farms face limitations in the form of higher expense due to anchoring needs and the issues of strong tides and waves causing damage and larger vertical displacements as compared to regular floating solar farms. This study explores the solution of a vertical curtain, forming a curtain-platform system with the solar farm, to act as an inexpensive breakwater against waves incident on the coastal solar farm. Experiments were carried out in a wave flume with a set-up simulating the curtain-platform system, using a vertical sheet representing the curtain and a perforated horizontal sheet representing the solar farm. Three parameters of the set-up were tested: surface penetration of vertical sheet, length of horizontal sheet and separation distance between the two sheets. Wave amplitudes were measured at six different locations using ultrasound sensors. The reflection and transmission coefficients as well as average vertical displacements of the horizontal sheet were obtained through MATLAB programs. The results show that for a surface penetration of ~40%, the vertical sheet can effectively attenuate the effect of incident waves. Different lengths of the horizontal sheet and separation distances between the sheets do not have a significant effect on attenuating the wave forces.